2022
DOI: 10.1097/aln.0000000000004442
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation Dynamics of Neuromuscular Blocking Drugs by Sugammadex

Abstract: Background The clinical actions of sugammadex have been well studied, but the detailed molecular mechanism of the drug encapsulation process has not been systematically documented. We hypothesized that sugammadex would attract rocuronium and vecuronium via interaction with the sugammadex side-chain “tentacles”, as previously suggested. Methods Computational molecular dynamics simulations were done to investigate docking of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Overall, the use of in silico technologies is a fruitful practice, not only to improve our understanding of drug‐receptor interactions at the molecular level, but also to pave the way for a brighter future in terms of cheaper and safer drugs. It has emerged that this could increase access to anesthesia for larger and diverse patient groups in developed or less developed countries and should be one of the main research goals in this area [17] …”
Section: Introductionmentioning
confidence: 99%
“…Overall, the use of in silico technologies is a fruitful practice, not only to improve our understanding of drug‐receptor interactions at the molecular level, but also to pave the way for a brighter future in terms of cheaper and safer drugs. It has emerged that this could increase access to anesthesia for larger and diverse patient groups in developed or less developed countries and should be one of the main research goals in this area [17] …”
Section: Introductionmentioning
confidence: 99%
“…However, unexpected and sudden arousal after sugammadex use baffles clinicians, and further investigation of the effect of sugammadex on arousal is required. Recent studies have reported that sugammadex can encapsulate other drugs, such as propofol and remifentanil, in addition to non-steroidal neuromuscular blockers 5 . Another study reported that low dose sugammadex administration (2 mg kg −1 ) provoked a lighter anesthesia depth pattern characterized by an increase in beta activity and a decrease in delta activity, without clinical signs of awakening when administering sugammadex in deep sevoflurane anesthesia 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of modern in silico computational chemistry and molecular modeling in this issue of Anesthesiology by Irani et al . 1 demonstrates the value that can be brought to our detailed understanding of pharmaceutical mechanisms at a molecular level and how this correlates with clinical effect. The authors stated three goals for their examination of sugammadex interactions with specific drugs: to examine the molecular dynamics of the encapsulation process of rocuronium and vecuronium by sugammadex; to validate the simulation technique by comparing the simulated binding strengths between sugammadex and 11 other compounds with previously published, experimentally obtained affinity data; and to characterize the patterns of sugammadex low-affinity binding with propofol.…”
mentioning
confidence: 99%
“…It is in light of this that other methods of molecular modeling were developed using more simplistic yet reasonably accurate methods of calculation. While there are many validated variations of the “forcefields” used to describe such intermolecular and intramolecular interactions that are both commercially available and open-source as implemented by Irani et al , 1 most consist of a series of parameters that have been developed to allow the bond length, bond angle, and bond torsion interactions to be accurately treated using the mathematics of the simple spring potential. These are further supplemented to consider equations involving the interactions between partial atomic charges, as well as hydrophobic interactions through various van der Waals potentials.…”
mentioning
confidence: 99%
See 1 more Smart Citation